2007
DOI: 10.1017/s0269964808000077
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of Flexible Servers in Two Tandem Queues With Operating Costs

Abstract: We consider two-stage tandem queuing systems with dedicated servers in each station and flexible servers that can serve in both stations. We assume exponential service times, linear holding costs, and operating costs incurred by the servers at rates proportional to their speeds. Under conditions that ensure the optimality of nonidling policies, we show that the optimal allocation of flexible servers is determined by a transition-monotone policy. Moreover, we present conditions under which the optimal policy ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…A small portion of the workforce is set to be available to float as generalists. The use of floaters potentially creates additional costs such as higher worker wages, set-up costs, set-up times, and longer working times (due to less task-specific experience) [45,46]. The level of flexibility increases linearly with increased portion of floaters in the system, yet costs associated with the use of floaters grow very fast, and can quickly outweigh the benefits.…”
Section: Floatersmentioning
confidence: 99%
See 2 more Smart Citations
“…A small portion of the workforce is set to be available to float as generalists. The use of floaters potentially creates additional costs such as higher worker wages, set-up costs, set-up times, and longer working times (due to less task-specific experience) [45,46]. The level of flexibility increases linearly with increased portion of floaters in the system, yet costs associated with the use of floaters grow very fast, and can quickly outweigh the benefits.…”
Section: Floatersmentioning
confidence: 99%
“…The use of floaters in clearing systems (no external arrival of jobs until originally scheduled jobs clear) has been well studied [46][47][48][49]. Particularly, dynamic allocation of floaters in clearing systems of two tandem queues have been modeled as DP problems.…”
Section: Floatersmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [25] showed the optimality of a switching-curve policy for the previous model with arrivals and no dedicated server in the upstream station and Pandelis [18] extended this result to the case when jobs may not require service at the downstream station and processing requirements are not the same in each station. Finally, Pandelis [17] studied a model with server operating costs in addition to holding costs and identified conditions under which the switching-curve structure of the optimal policy is preserved.…”
Section: Introductionmentioning
confidence: 99%
“…First, we include in the model costs that not only depend on the state of the process but on the actor-action pair as well. Such a system is the two-stage queueing model with multiple collaborating servers considered in Pandelis (2008a), where each server incurs operating costs at rates depending on the queue where he is allocated. We show that the same action is optimal for all actors if the operating costs rates are proportional to the actors' speeds, with the proportionality constants being functions only of the actions.…”
Section: Introductionmentioning
confidence: 99%